2008
DOI: 10.1080/01635580802381477
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvedic Medicine Constituent Withaferin A Causes G2 and M Phase Cell Cycle Arrest in Human Breast Cancer Cells

Abstract: Withaferin A (WA) is derived from the medicinal plant Withania somnifera that has been safely used for centuries in the Indian Ayurvedic medicine for treatment of various ailments. We now demonstrate that WA treatment causes G2 and mitotic arrest in human breast cancer cells. Treatment of MDA-MB-231 (estrogen-independent) and MCF-7 (estrogen-responsive) cell lines with WA resulted in a concentration-and time-dependent increase in G2-M fraction, which correlated with a decrease in levels of cyclin-dependent kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 38 publications
14
108
0
Order By: Relevance
“…14,18,20,30 Accordingly we also found that WA treatment resulted in decreased expression of CDK1 but not cyclin B1 in both LY-10 and LY-3 cells lines, which may lead to G 2 /M phase arrest. Results of WA treatment on SudHL-6 cells were consistent with the G 2 /M phase arrest seen in melanoma, glioblastoma, and cervical cancer cells.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…14,18,20,30 Accordingly we also found that WA treatment resulted in decreased expression of CDK1 but not cyclin B1 in both LY-10 and LY-3 cells lines, which may lead to G 2 /M phase arrest. Results of WA treatment on SudHL-6 cells were consistent with the G 2 /M phase arrest seen in melanoma, glioblastoma, and cervical cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…14 Several studies found that WA stimulates apoptosis through restoring p53 levels and thus activating Bax and other pro-apoptotic Bcl-2 family proteins to induce apoptosis of cervical cancer cells, 18 or by enhancing levels of the proapoptotic factor, Par-4, and downstream caspase activation in prostate cancer cells. 19 In most cancer cell lines WA inhibits the proliferation of tumor cells through a G 2 /M phase cell cycle arrest, 20 and inhibits the activation of NF-kB via interaction with the IKKg subunit preventing IkB phosphorylation. 21,22 In pancreatic cancer cells, Yu et.…”
Section: Introductionmentioning
confidence: 99%
“…After H 2 O 2 exposure for 24 h, 50 -80 % cell viability was observed at extract concentrations from 6.11 µg/mL to 100 µg/mL, compared with the negative control (H 2 O 2 alone), with 50 and 100 µg/mL extract concentrations showing the greatest improvement compared with the negative control (p<0.001). At the highest extract concentration (200 µg/mL) the cytoprotective effects were abolished, due, perhaps, to direct cytotoxic and antiproliferative properties of W. somnifera being expressed at high concentrations (Sabbaraju et al, 2006;Stan et al, 2008). .…”
Section: Effect Of W Somnifera Extract On Viability Of Dpc12 Cells Amentioning
confidence: 99%
“…The eukaryotic cell cycle is strictly regulated by a class of cyclins and cyclindependent kinases (CDKs) [31] . The progression from G 2 to mitosis is controlled by the mitosispromoting factor, which comprises a complex of Cdc2 (CDK1) and cyclin B [32][33][34][35] . During G 2 /M transition, CDK1 activation requires an association with cyclin B1 and phosphorylation at Thr 161 by CDK-activating kinase (CAK), whereas the CDK1/ cyclin B complex is kept inactive by phosphorylation on Thr 14 or Tyr 15 of CDK1 by kinase Wee1 and Myt1 [36] .…”
Section: Wwwnaturecom/aps Zheng Se Et Almentioning
confidence: 99%